2001
DOI: 10.1080/10459880109603330
|View full text |Cite
|
Sign up to set email alerts
|

Intervention Assistance: Is It Substance or Symbolism?

Abstract: Made available courtesy of Taylor and Francis: http://www.tandf.co.uk/journals/ ***Reprinted with permission. No further reproduction is authorized without written permission from Taylor and Francis. This version of the document is not the version of record. Figures and/or pictures may be missing from this format of the document.*** Article: In 1990, the Commonwealth of Pennsylvania revised its special education standards to require interventionassistance services (i.e., Instructional Support Teams or ISTs) fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…Although child study teams offer many advantages (Rock & Zigmond, 2001), if they are not part of wider systems of change within a school, they can become simply another stage of special education referral.…”
Section: The Child Study Processmentioning
confidence: 99%
“…Although child study teams offer many advantages (Rock & Zigmond, 2001), if they are not part of wider systems of change within a school, they can become simply another stage of special education referral.…”
Section: The Child Study Processmentioning
confidence: 99%
“…Team-based problem solving is best understood as a collaborative effort (e.g., administrators, teachers, support personnel, parents, and ideally the student, see Martin, Marshall, & De Pry, 2008) that seeks to understand the academic and/or social problem and identify support strategies that are evidenced-based, contextually relevant, and selected with success in mind. RtI models use this process to support teachers who have requested help, to identify and understand emerging data patterns, to develop research-based interventions, and to measure progress over time and across settings (Colorado Department of Education, 2008;Gravois & Rosenfield, 2006;Rock & Zigmond, 2001;Safran & Safran, 1996).…”
Section: Triangle Of Support: An Integrative Modelmentioning
confidence: 99%
“…Problemsolving teams have gone by many names over the years, examples include: Prereferral Teams, Intervention Assistance Teams, Student Support Teams, Instructional Support Teams, to name a few. All seem to operate following a similar pattern (a) to establish a problem-solving process and assist teachers, (b) to implement general education "solutions" prior to referral to special education, (c) to screen students for special education, and (d) to support teachers who work with students on Individualized Education Plans (IEPs) (Rock & Zigmond, 2001). Team composition can include an administrator, general education and special education teachers, and other support personnel, such as a school psychologist or school counselor.…”
Section: Problem Resolution: Not Problem Studentsmentioning
confidence: 99%
“…Some research has suggested that a larger than expected number of students considered by problem-solving teams are retained or referred to special education in subsequent years (Rock & Zigmond, 2001). Conversely, these procedures should ensure that ELLs who do not respond to highquality interventions are rapidly identified and should prevent either IAT processes or the belief that a struggling ELL "just needs time to adjust and learn English" from being a barrier to an appropriate special education referral.…”
Section: Fidelity Of Implementation and Evaluationmentioning
confidence: 99%